IMPLEMENTASI SISTEM INFORMASI MANAJEMEN DALAM MENDUKUNG PELAYANAN ADMINISTRASI DI SMA NEGERI 4 JAYAPURA - Darsono, Kevin Putra (Universitas Cenderawasih, 2024)
The implementation of the Education Management Information System (SIMDIK) is an important need for educational institutions to improve service quality, efficiency, and competitiveness in the era of globalization, in accordance with regulations such as Law No. 20 of 2003 concerning the National Education System and Permendiknas No. 19 of 2007 concerning Education Management Standards. This article aims to analyze the implementation of management information systems in SMA Negeri 4 Kota Jayapura, analyzing the factors that support and hinder it. This type of research is descriptive qualitative. The type of research used is field research, where this research is conducted in a particular environment, precisely at SMA Negeri 4 Kota Jayapura. data is collected through in-depth interviews with principals, teachers, students, and administrative staff, as well as direct observation to understand the supporting and inhibiting factors in the implementation of SIMDIK. This research uses Edward III Implementation Theory. Measurement indicators include communication, resources, layout and organizational structure. The implementation of management information systems is very important in educational institutions, especially in SMA Negeri 4 Jayapura city, where data processing applications are used, especially Dapodik and IT technology to support the learning process by providing educational services by facilitating learning practices using technology infrastructure, such as computer-integrated learning facilities.